It looks like you're new here. If you want to get involved, click one of these buttons!

- 32.1K All Categories
- 27.1K LSAT
- 16.5K General
- 5.1K Logical Reasoning
- 1.3K Reading Comprehension
- 1.7K Logic Games
- 72 Podcasts
- 193 Webinars
- 9 Scholarships
- 193 Test Center Reviews
- 2K Study Groups
- 108 Study Guides/Cheat Sheets
- 2.4K Specific LSAT Dates
- 6 June 2024 LSAT
- 1 April 2024 LSAT
- 11 February 2024 LSAT
- 23 January 2024 LSAT
- 37 November 2023 LSAT
- 41 October 2023 LSAT
- 12 September 2023 LSAT
- 38 August 2023 LSAT
- 27 June 2023 LSAT
- 1 August 2024 LSAT
- 30 Sage Advice
- 4.8K Not LSAT
- 3.9K Law School Admissions
- 11 Law School Explained
- 9 Forum Rules
- 574 Technical Problems
- 275 Off-topic

1 Like

jane1010
Free Trial Member

hi there,

i have a question on diagramming multiple conditionals: e.g., Q#15, section 1 of PT #63 (june 2011), choice B states, "if someone tells the same lie to two different people, then neither of those lied to is owed an apology unless both are." i know this is not the correct answer choice but i had a question as to how we'd diagram a multi-part conditional statement like this. would the correct way be:

someone tells the same lie to two different people --> (at least one owed apology --> both owed apology)? if so, what would be the contrapositive of the entire sentence? i never dealt with a conditional within a conditional so any advice you have would be greatly appreciated!

thanks in advance!

i have a question on diagramming multiple conditionals: e.g., Q#15, section 1 of PT #63 (june 2011), choice B states, "if someone tells the same lie to two different people, then neither of those lied to is owed an apology unless both are." i know this is not the correct answer choice but i had a question as to how we'd diagram a multi-part conditional statement like this. would the correct way be:

someone tells the same lie to two different people --> (at least one owed apology --> both owed apology)? if so, what would be the contrapositive of the entire sentence? i never dealt with a conditional within a conditional so any advice you have would be greatly appreciated!

thanks in advance!

## Comments

The contrapositive would be if you negate the second condition, contradicting the truth of the condition. According to the second condition, if you must apologize to someone, you must apologize to both. If you can prove a situation where you must apologize to someone, but not necessarily both, then it cannot have been an apology for an identical lie told to two people.

If you can contradict the truth of the second condition, then the first condition could not have existed.

I hope I wasn't confusing.

given: "someone tells the same lie to two different people --> (at least one owed apology --> both owed apology)"

contrapositive: someone tells the same lie to two different people --> (both not owed apology --> neither owed apology)

and this is because the negation of a conditional, A --> B is A -->~B, correct?

It follows the same method as a normal condition:

Normal condition: A --> B

Negation: ~B --> ~A

Double conditional: A --> (C --> D)

Negation: First show we are discussing case where C-->D doesn't apply (i.e. C-->~D or ~D-->C). Once the (C-->D) rule is inapplicable, A must be as well.

There's a lesson on embedded conditionals:

http://7sage.com/lesson/mastery-embedded-conditional

Also a lesson on negating conditionals:

http://7sage.com/lesson/advanced-negate-all-statements/

Okay, that's all. Please carry on!

So... just to clarify:

If we're starting out with "

if someone tells the same lie to two different people, then neither of those lied to is owed an apology unless both are,"I'd have diagrammed it like this:

Tells same lie to both→ (~Both owed apol→~1 owed apoland~2 owed apol)Getting rid of the embedded conditional (i.e., taking out the parentheses) yields:

Tells same lie to bothand~Both owed apol→~1 owed apoland~2 owed apolSo I get the contrapositive as being:

1 owed apol.or2 owed apol→~Tells same lie to bothorBoth owed apolIf this looks okay, I guess I'm not sure where negating an 'all statement' (the 2nd referenced video lesson) would come into play?

Could someone help me understand this?